Disease Free Survival of Stage I Endometrial Cancer after Surgery with or without Adjuvant Treatment - Moradokkasem, Woraluk; Saeaib, Nungrutai; Liabsuetrakul, Tippawan (Folia Medica Indonesiana, 2019)
This study aimed to define the disease free survival (DFS) and factors associated with recurrence in stage I endometrial cancer after surgery with and without adjuvant treatment. The demographic data, pathological results, adjuvant treatment (AT) and the outcome of patients with endometrial cancer stage I after surgery in Songklanagarind Hospital between January 2002 and July 2014 were collected. The DFS was analyzed by survival analysis and represented by Kaplan–Meier curves. The difference of DFS between AT and non-adjuvant treatment (NAT) groups was tested by the log-rank test. Distributions of risk factors by AT and recurrent status were analyzed using chi-square or Fisher exact tests for discrete factors, and unpaired t or Wilcoxon rank-sum tests for continuous factors. The 5-year DFS was; 91.6%, from a total of 268 patients. DFS in the NAT group was significantly better than that in the AT group (95.2 versus 86.5%, p-value = 0.01). Factors associated with recurrence in the NAT group were age, tumor grading, tumor size, and presence of lymphovascular involvement. Among the AT group, age and ratio of myometrial invasion were associated with recurrence. DFS in NAT was better than in AT and the potential factors associated with recurrence, after surgery with or without AT, were not the same.